Black Pepper (Piper nigrum) for Tobacco Withdrawal: A Case Report - Weleff, Jeremy; Dore, Samyukta; Anand, Akhil; Barnett, Brian S. (Case Reports in Psychiatry, 2022)
Tobacco use continues to be one of humanity’s most significant public health concerns, causing more than 8-million deaths annually. Existing treatments for tobacco use disorder are limited in efficacy and there is a strong need for identifying effective novel treatments. Small clinical trials indicate that black pepper (Piper nigrum) essential oil may be helpful for treating nicotine withdrawal and craving. However, we are unaware of any cases reporting the use of black pepper for these purposes in nonresearch settings. Here we present the case of a patient who inhaled combusted black pepper to self-medicate nicotine withdrawal when lacking access to tobacco cigarettes while incarcerated. Based on our patient’s report, inhalation of combusted black pepper may have alleviated his tobacco withdrawal and cravings by reducing his automatic motor urge to smoke, quelling withdrawal-associated anxiety, and mimicking the sensorimotor experience of smoking tobacco cigarettes. Notably, our patient reported that inhalation of combusted black pepper for treatment of nicotine craving and withdrawal was common in his correctional facility. Though combusted black pepper is highly unlikely to be an appealing treatment outside of a correctional setting, this case suggests that further investigation of vaporized black pepper essential oil for tobacco cessation may be warranted.